Spray-dried microporous Pt/TiO2 degrades 4-chlorophenol under UV and visible light. Issue 4 (August 2019) - Khan, Hayat; Usen, Ndifreke; Boffito, Daria C.
Highlights: Spray-drying produced meso-macroporous Ptx /TiO2 with high surface area (332 m 2 /g). For x ≤ 0.8 and x > 0.8 wt.% tensile and compressive strain occur, respectively. Photoluminescence intensity trend is T > Pt0.4 T > Pt1.2 T > Pt0.8 T. The catalysts have highly adsorptive (001) planes exposed, Pt0.8 T having the most. Pt0.8 T degrades 60% and 40% 4-chlorophenol under UV and Vis light, respectively. Abstract: We prepared nanoparticles of a microporous Pt catalyst over TiO2 (Ptx T, x= 0.2–0.8 wt. %) with exposed (001) facets by sol-gel followed by spray-drying of a Ti(oBu)4 -C2 H6 O and H2 PtCl6 -H2 O mixture. The characterization methods were XRD, FTIR, BET, SEM-EDX/TEM, UV-DRS, Photoluminescence (PL) and Raman spectroscopy. XRD analysis confirmed that all samples consisted of mainly anatase with little rutile, while pure TiO2 (T) consisted of only anatase after calcination at 550° C. The deposition of Ptx on TiO2 produces tensile strain for x < 0.8 wt.%, while further increase causes compressive strain. The absorption wavelength of Ptx -TiO2 shifted to greater values compared to control T (UV–vis DRS spectroscopy). The Ptx T powders exhibited lower PL intensity than T, since the addition of Pt nanoparticles up to 0.8% captures the photogenerated electrons. The broadening of the Raman peak and the small frequency shift for the Raman bands (1-Eg and B1g ) indicate that there are oxygen vacancies and crystal lattice distortions. The degradation of 4-chlorophenol under UV and visible light was the model reaction for the photocatalytic activity. Radical scavenging experiments demonstrated that superoxide (O 2 − ) anions followed by photogenerated h + species are mainly responsible for the degradation of 4-chlorophenol. The Ptx T samples degrade up to 40% more 4-chlorophenol under UV and Vis irradiation than Degussa P25 and T as a consequence of the high crystallinity, homogenous distribution of Pt, as well as surface area >300 m 2 /g and spherical morphology. Based on the data, we propose a photocatalytic mechanism.